802.11p Optimization for Delay Sensitive in Non-Safety Messages in VANETs - Shamsul J Elias; M.N.M Warip; M. Elshaikh; M. Yusof Darus; R Badlishah Ahmad (Indonesian Journal of Electrical Engineering and Computer Science, 2018)
Vehicle density and high vehicle mobility are variables that measured the performance of Vehicular Ad Hoc Network (VANET) in unpredictable traffic data transmission environment. This paper is focused on non-safety messages transmission mainly for delay in time in test-bed simulation environment. Network optimization is an approach to evaluate the existing congestion control protocols and other network parameters for outlining a newly enhanced congestion control protocols. This paper presents a city and highway traffic data transmission scenarios for optimizing delay sensitivity utilizing the Taguchi method.  The avareage data transmission on delay is performance indicator applying OMNeT++ simulation tools. The optimization process could be achieved once the best fit performance parameters are being identified. The best fit performance values could conclude the optimal and efficient congestion control networks. The packet sizes are the main control factors for this test-bed experiment focusing on non-safety messages which are delay sensitive.